Scientific research in view of Quran and the creation of Allah s.w.t. - Taha Alshaikhli, Imad Fakhri (2018)
Scientific research is the backbone of all discoveries, inventions, and creation of facts, ideas, reasons, devices, tools, etc. One of the main sources of doing a good research is having access to good, comprehensive, reliable, and up to date references, which can be a problem in many cases. In this talk I will try to show the importance of the holy book Quran as the best reference of the past, present, and future. Giving examples of some proved cases from Quran. In addition to highlight the importance of having insight of the creation of the creator like ourselves, surrounding world, other creations as a means of advancing our lives. Our own research results will be shown too. Examples will be given from Quran and from the creation of the creator as well as some examples of what can be investigated in future.